An Overview on Dry Eye Treatment: Approaches for Cyclosporin A Delivery - Burçin Yavuz; Sibel Bozdağ Pehlivan; Nurşen Ünlü (The Scientific World Journal, 2012)
Dry eye syndrome (DES, Keratoconjunctivitis sicca) is a common disorder of the tear film caused by decreased tear production or increased evaporation. Changes in tear composition also promote inflammation on the ocular surface by various mechanisms. Artificial tear drops, tear retention treatment, stimulation of tear secretion, or anti-inflammatory drugs may be used for dry eye treatment according to the severity of the disease. For untreated patients, the risk of ocular infection increases at considerable level and clinical course of the disease may proceed up to infection, corneal ulcer, and blindness. Artificial tears and/or punctual occlusions are used for tear replacement or preservation. New treatment approaches are designed to modify the underlying disease process. For the treatment of severe dry eye disease, cyclosporin A (CsA), the first one of the new generation immunomodulatory drugs, which has an anti-inflammatory effect, is frequently used. CsA has immunosuppressive effects following systemic application. Following local administration of CsA, it is expected to obtain effective drug concentration at the target area and to avoid the various side effects associated with systemic delivery. Microspheres, implants, and liposomes have been developed for administration of CsA subconjunctivally in order to enhance its efficiency.